1997
DOI: 10.1002/(sici)1096-8652(199711)56:3<189::aid-ajh11>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral infarct associated with factor V Leiden mutation in a boy with hemophilia A

Abstract: An 11-year-old boy with mild hemophilia A was admitted to our hospital because of focal convulsions. Magnetic resonance imaging showed an old occipital infarct. Protein C, S, antithrombin III, anticardiolipin antibodies and fibrinogen were normal. Heterozygosity for factor V Leiden mutation was detected. We suggest that factor V Leiden mutation should be studied in hemophiliacs with thrombosis.Am.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Venous thrombosis is an important cause of hospital acquired morbidity and mortality [3]. It is associated rarely with patients of hemophilia A [1,2,[4][5][6][7]. Several risk factors have been described in medical literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Venous thrombosis is an important cause of hospital acquired morbidity and mortality [3]. It is associated rarely with patients of hemophilia A [1,2,[4][5][6][7]. Several risk factors have been described in medical literature.…”
Section: Discussionmentioning
confidence: 99%
“…Hemophilia A is a hereditary hemorrhagic disease characterized by deficiency of coagulation Factor VIII. Venous thrombosis in patients with hemophilia A has been rarely encountered in medical literature [1,2,[4][5][6][7] and it is an important cause of hospital acquired morbidity and mortality [3]. In this case report we present the onset of deep vein thrombosis in a one year old child with hemophilia A.…”
Section: Introductionmentioning
confidence: 90%
“…Occurrence of arterial or venous thrombosis in these patients is rare and would seem to be paradoxical to the underlying disease. Few cases of thrombotic events in patients with inherited coagulation disorders have been reported in the literature [1–5]. We describe a 25‐year‐old man with severe haemophilia A, who developed spontaneous deep vein thrombosis of the left upper limb in this case report.…”
Section: Introductionmentioning
confidence: 90%
“…Other reports have also shown that even patients with severe haemophilia are prone to the development of venous thrombosis after insertion of central venous catheters for prolonged periods (Blanchette et al ., 1996; Opanasenko & Voloshin; Journeycake et al ., 2001). There are a few reports of haemophilia patients with the FV Leiden mutation developing thrombosis (Olcay et al ., 1997; Purthi et al ., 2000). However, our patient had no thrombophilia markers.…”
mentioning
confidence: 99%